Mental health treatment to reduce HIV transmission risk behavior: a positive prevention model. - Sikkema, Kathleen J; Watt, Melissa H; Drabkin, Anya S; Meade, Christina S; Hansen, Nathan B; Pence, Brian W (AIDS and behavior, 2010)
Secondary HIV prevention, or "positive prevention," is concerned with reducing HIV transmission risk behavior and optimizing the health and quality of life of people living with HIV/AIDS (PLWHA). The association between mental health and HIV transmission risk (i.e., sexual risk and poor medication adherence) is well established, although most of this evidence is observational. Further, a number of efficacious mental health treatments are available for PLWHA yet few positive prevention interventions integrate mental health treatment. We propose that mental health treatment, including behavioral and pharmacologic interventions, can lead to reductions in HIV transmission risk behavior and should be a core component of secondary HIV prevention. We present a conceptual model and recommendations to guide future research on the effect of mental health treatment on HIV transmission risk behavior among PLWHA.
Keywords: Behavior Therapy; HIV Infections; Humans; Mental Disorders; Mental Health; Models, Biological; Patient Compliance; Risk-Taking; Sexual Behavior